Editor's Choice – Systematic Review and Narrative Synthesis of Randomised Controlled Trials Supporting Implantable Devices for Vascular and Endovascular Procedures. (July 2022) - Wardle, Bethany G.; Botes, Azel; Ambler, Graeme K.; Rudd, Sarah; Qureshi, Mahim; Bosanquet, David C.; Hinchliffe, Robert J.; Twine, Christopher P.
Abstract : Objective: To identify implantable devices currently used for vascular and endovascular procedures, to ascertain how many have randomised controlled trial (RCT) evidence available, and to assess the quality of that evidence. Data Sources: MEDLINE, Embase, DARE, PROSPERO, clinical trial registries, and Cochrane databases. Review Methods: A list of current devices used in both vascular and endovascular procedures was generated by searching conference proceedings, manufacturer catalogues, and websites. MEDLINE, Embase, DARE, PROSPERO, clinical trial registries, and Cochrane databases were searched from inception up to June 2020. The primary outcome was the availability of RCTs to support the use of a vascular implantable device. RCTs were then quality assessed using the Cochrane risk of bias tool. Results: A total of 116 current vascular implantable devices were identified. The systematic literature review identified 165 RCTs. Eighty-three of the RCTs (50.3%) applied to 33 of the 116 (28.4%) current implantable devices. When grouped by device type, eight of the 13 types (62%) had at least one RCT performed. There was a high risk of bias across the majority of the RCTs, with only nine (5.4%) deemed to be at low risk of bias. Only 22 (13.3%) RCTs had a clear safety outcome. Conclusion: Sixty-two per cent of implantable device types for use in vascular and endovascular interventions had at least one RCT available to show equivalence to previous devices or safety. RCTs were generally of low quality and are decreasing in frequency with time. With medical implantable device failure being increasingly recognised as causing significant harm to patients worldwide, there is a clear need for a more robust implantable device regulation and approval systems.